Sigma-1 Receptor: A Potential Therapeutic Target for Traumatic Brain Injury - Shi, Mingming; Chen, Fanglian; Chen, Zhijuan; Yang, Weidong; Yue, Shuyuan; Zhang, Jianning; Chen, Xin (Frontiers in Cellular Neuroscience, 2021)
The sigma-1 receptor (Sig-1R) is a chaperone that mainly resides at the mitochondria-associated membranes (MAMs) and acts as a dynamic pluripotent modulator regulating cellular pathophysiological processes. Multiple pharmacological studies have confirmed the beneficial effects of Sig-1R activation on cellular calcium homeostasis, excitotoxicity modulation, reactive oxygen species (ROS) clearance and endoplasmic reticulum (ER), mitochondria and MAMs structural and functional stability. Sig-1R is expressed broadly in cells of the central nervous system (CNS) and has been reported to be involved in various neurological disorders. TBI-induced secondary injury involves complex and interrelated pathophysiological processes such as cellular apoptosis, glutamate excitotoxicity, inflammatory responses, endoplasmic reticulum stress, oxidative stress and mitochondrial dysfunction. Thus, given the pluripotent modulation of the Sig-1R in diverse neurological disorders, we hypothesized that the Sig-1R may affect a series of pathophysiology after TBI. This review summarizes the latest emerging roles of Sig-1R and its mechanism in various pathophysiological processes of multiple central nervous system (CNS) diseases and discusses the potential therapeutic role of Sig-1R in TBI.